Variation in Ovine KRTAP13-3 and Its Association with Wool Characteristics in Chinese Tan Sheep - Lingrong Bai; Huitong Zhou; Jinzhong Tao; Jon G. H. Hickford (Animals)
Understanding the genetic factors that influence wool quality is essential for enhancing wool quality and uniformity. This study investigated the KRTAP13-3 gene in Chinese Tan sheep, a breed known for its unique wool characteristics. We analysed 232 sheep and revealed five previously identified sequence variants of KRTAP13-3 and then modelled to ascertain whether there was any association between the nucleotide sequence variation and variation in mean fibre diameter (MFD), fibre diameter standard deviation (FDSD), coefficient of variation of fibre diameter (CVFD), and mean fibre curvature (MFC). Twelve genotypes were observed, with the five variants having frequencies that ranged from 64.0% to 1.1%. Among the four variants with frequencies above 5%, nucleotide sequence variation was associated with heterotypic hair fibre diameter variation. The most common variant (A) was linked to increased FDSD and CVFD, while two other variants (B and D) revealed trends towards being associated with decreased CVFD. No associations were found with variation in the fine wool fibres from the Tan sheep. This suggests that KRTAP13-3 plays a role in regulating heterotypic hair fibre diameter variability and that it could possibly be a gene marker for improving wool traits.